2020
DOI: 10.3390/ijerph17186934
|View full text |Cite
|
Sign up to set email alerts
|

Personal Music Players Use and Other Noise Hazards among Children 11 to 12 Years Old

Abstract: Exposure to loud music—due to widespread personal music players (PMPs) and noisy leisure activities—are major risk factors for noise induced hearing loss (NIHL) in adolescents. However, there is little evidence of the impact of noise on the hearing of younger children. This study aimed to explore an association between PMP use and hearing, and to identify other sources of noise among children. The study sample consisted of 1032 children aged 11–12 years old. Hearing thresholds were determined from 0.5 to 8 kHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…In addition, hidden hearing loss with abnormal brainstem response latency or outer hair cell dysfunction, which could be evaluated using distortion-product optoacoustic emissions or auditory brainstem response, was not considered in this study. It was reported that personal music player use and noise exposure were related to the experience of tinnitus in children, although it did not frequently accompany hearing loss [ 27 ]. Central deafferentation due to cochlear damage, which was measured by a threshold equalizing noise test and a pitch scaling task, existed even in the tinnitus patients with normal audiograms of 0.25, 0.5, 1, 2, 3, 4, 5, 6, and 8 kHz [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hidden hearing loss with abnormal brainstem response latency or outer hair cell dysfunction, which could be evaluated using distortion-product optoacoustic emissions or auditory brainstem response, was not considered in this study. It was reported that personal music player use and noise exposure were related to the experience of tinnitus in children, although it did not frequently accompany hearing loss [ 27 ]. Central deafferentation due to cochlear damage, which was measured by a threshold equalizing noise test and a pitch scaling task, existed even in the tinnitus patients with normal audiograms of 0.25, 0.5, 1, 2, 3, 4, 5, 6, and 8 kHz [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the 11 cohort studies that evaluate relationships between gaming and hearing loss and/or tinnitus are given in table 1. [23][24][25][26][27][28][29][30][31][32][33] Ten cohort studies were crosssectional, and one was longitudinal. Six studies were conducted in children (<19 years), [25][26][27][28][29][30] three were conducted in adults (≥19 years), 24 32 33 and two were conducted in adults and children.…”
Section: Cohort Studiesmentioning
confidence: 99%
“… 8 In Poland, 11.5% of 643 youths aged 13 to 18 years had hearing loss at 4 or 6 kHz, and it was significantly higher in those with heavy exposure to loud music (16.3%) than in those with mild exposure (10.7%). 192 …”
Section: Evidence-based Evaluation and Diagnosis Of Hearing Loss In C...mentioning
confidence: 99%